2015
DOI: 10.1037/a0038385
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and statistical information in causal structure learning.

Abstract: Three experiments examined children’s and adults’ abilities to use statistical and temporal information to distinguish between common cause and causal chain structures. In Experiment 1, participants were provided with conditional probability information and/or temporal information and asked to infer the causal structure of a 3-variable mechanical system that operated probabilistically. Participants of all ages preferentially relied on the temporal pattern of events in their inferences, even if this conflicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 80 publications
1
20
1
1
Order By: Relevance
“…People rule out backwards causation, assuming that effects cannot precede causes (Burns and McCormack, 2009;Greville and Buehner, 2010;Bramley et al, 2014). Work in the cognitive sciences on the use of time in causal judgments has focused on point events separated by delays-that is, events like explosions and collisions that occur at particular times but with negligible duration (Shanks et al, 1989;Griffiths, 2004;Lagnado and Sloman, 2006;Pacer and Griffiths, 2012;McCormack et al, 2015). From this line of work, we have learned more than just that temporal order is relevant for causal direction.…”
Section: Timementioning
confidence: 99%
“…People rule out backwards causation, assuming that effects cannot precede causes (Burns and McCormack, 2009;Greville and Buehner, 2010;Bramley et al, 2014). Work in the cognitive sciences on the use of time in causal judgments has focused on point events separated by delays-that is, events like explosions and collisions that occur at particular times but with negligible duration (Shanks et al, 1989;Griffiths, 2004;Lagnado and Sloman, 2006;Pacer and Griffiths, 2012;McCormack et al, 2015). From this line of work, we have learned more than just that temporal order is relevant for causal direction.…”
Section: Timementioning
confidence: 99%
“…Although these studies tend to focus on the tests people generate during active causal learning, the mechanisms discussed in previous sections may also contribute to gains in learning relative to passive observation. For instance, because effects follow their causes in time, generating a causal intervention may aid in co‐ordinating attention to the presentation of the effect (Lagnado & Sloman, ; see also McCormack, Frosch, Patrick, & Lagnado, ). Alternatively, deciding how to intervene on a system (i.e., designing an experiment) may lead learners to generate causal explanations, an elaborative process that has been shown to lead to improved retention (Dunlosky et al, ) but which may be less likely when interventions are simply observed.…”
Section: Broader Implicationsmentioning
confidence: 99%
“…Perhaps, the bidirectional relationship between time and causality is a fundamental invariant property of our perceptual and cognitive system, in which case we would expect binding to be present from early childhood. There appears to be a privileged relation between time and causation in children: children prioritize temporal information over other types of cues such as statistical information (McCormack, Frosch, Patrick, & Lagnado, ) and knowledge of causal mechanisms (Schlottmann, ), suggesting that the use of temporal information to infer causality may be automatic and developmentally basic (Schlottmann, Allen, Linderoth, & Hesketh, ). It is thus possible that the close relation between time and causation seen in childhood works both ways: that children not only rely heavily on temporal cues in forming causal beliefs, but that such beliefs also affect their perception of time.…”
Section: Introductionmentioning
confidence: 99%